FORMULATING KEY PERFORMANCE INDICATORS FOR AN INTEGRATED ENTERPRISE MANAGEMENT SYSTEM USING A SUSTAINABLE DEVELOPMENT BALANCED SCORECARD (Development Service Industry Management, 2024)
The alignment of business strategies with the United Nations' Sustainable Development Goals has become increasingly essential. Companies are now required to adopt robust mechanisms to track and report on sustainability performance. The integration of KPIs based on a sustainable development balanced scorecard directly addresses this need, offering a structured framework for embedding sustainability metrics into enterprise management systems.The process of developing and implementing sustainable KPIs fosters a culture of innovation and continuous improvement. Enterprises are encouraged to explore new ways to enhance their sustainability performance, driving innovation in products, services, and operational processes.The aim of this paper is to develop key performance indicators for an integrated enterprise management system utilizing a balanced scorecard approach that incorporates sustainable development indicators.A sustainable development balanced scorecard serves as a strategic tool to assess and manage organizational performance in alignment with sustainable development goals and objectives.In determining the KPIs for the integrated management system, a modified balanced scorecard is proposed to account for stakeholder interactions and focus on sustainable development goals. This approach aligns sustainability objectives with organizational-level business strategies, promotes social responsibility, and supports informed decision-making for sustainable development. The sustainable development balanced scorecard includes the subsystems: "Results," "Stakeholders," "Processes," and "Enablers," with KPIs identified through multidimensional factor analysis. Establishing key performance indicators within these subsystems will harmonize the economic, social, and environmental goals of the enterprise, fostering a holistic approach to sustainable development.
Keywords: management; management system; enterprise; balanced scorecard; sustainable development